Implikasi Yuridis Peraturan Pemerintah Nomor 28 Tahun 2025 Terhadap Kewenangan Perizinan Berusaha Daerah - Rezza Dwi Purnama Gunawan (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the ratio legis underlying the enactment of Government Regulation Number 28 of 2025 and its juridical implications for the construction of regional government authority in Indonesia, particularly concerning the shift from attributive to merely administrative mandate authority. The research employs a doctrinal legal research method, collecting data through library research on primary legal materials, including the 1945 Constitution, Law Number 23 of 2014 on Regional Government, and Government Regulation Number 28 of 2025, supplemented by secondary materials from peer-reviewed journal articles and tertiary legal references, analyzed qualitatively using statute and conceptual approaches. The results reveal that the regulation adopts an economic analysis of law framework prioritizing national standardization and digital efficiency through mechanisms such as fictive positive approval and post-audit supervision, yet substantially reduces regional discretion and fiscal independence through centralized licensing retribution. These findings indicate a constitutional dissonance between investment acceleration and the principle of the widest possible regional autonomy, suggesting that asymmetric decentralization mechanisms are necessary to restore balance between central efficiency and local economic sovereignty.